2014
DOI: 10.7717/peerj.284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of2H and18O water isotopes in kinesin-1 gliding assay

Abstract: We show for the first time the effects of heavy-hydrogen water (2H2O) and heavy-oxygen water (H218O) on the gliding speed of microtubules on kinesin-1 coated surfaces. Increased fractions of isotopic waters used in the motility solution decreased the gliding speed of microtubules by a maximum of 21% for heavy-hydrogen and 5% for heavy-oxygen water. We also show that gliding microtubule speed returns to its original speed after being treated with heavy-hydrogen water. We discuss possible interpretations of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Due to the natural occurrence of D 2 O and differences in chemical structure and physical properties compared to H 2 O, researchers have used D 2 O to study the effects of water on biomolecules and cells. Studies include effects of D 2 O on tobacco seed growth (Lewis, 1934), IgE-Mediated histamine release from human leukocytes (Gillespie & Lichtenstein, 1972), actin filament velocities (Chaen et al, 2001), protein flexibility (Cioni & Strambini, 2002), human pancreatic tumor cells (Hartmann et al, 2005), phospholipid membranes (Beranova et al, 2012), kinesin-1 gliding assay (Maloney, Herskowitz & Koch, 2014), and stabilization of tubulin as observed previously in microtubule gliding assays (Panda et al, 2000) and in biochemical experiments on isolated tubulin proteins from beef brain (Houston et al, 1974) and goat brain (Das et al, 2008). Microtubules are polarized polymers of α / β tubulin heterodimers and undergo alternating phases of growth and shrinkage with sudden transitions between the two (Bartolini et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the natural occurrence of D 2 O and differences in chemical structure and physical properties compared to H 2 O, researchers have used D 2 O to study the effects of water on biomolecules and cells. Studies include effects of D 2 O on tobacco seed growth (Lewis, 1934), IgE-Mediated histamine release from human leukocytes (Gillespie & Lichtenstein, 1972), actin filament velocities (Chaen et al, 2001), protein flexibility (Cioni & Strambini, 2002), human pancreatic tumor cells (Hartmann et al, 2005), phospholipid membranes (Beranova et al, 2012), kinesin-1 gliding assay (Maloney, Herskowitz & Koch, 2014), and stabilization of tubulin as observed previously in microtubule gliding assays (Panda et al, 2000) and in biochemical experiments on isolated tubulin proteins from beef brain (Houston et al, 1974) and goat brain (Das et al, 2008). Microtubules are polarized polymers of α / β tubulin heterodimers and undergo alternating phases of growth and shrinkage with sudden transitions between the two (Bartolini et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the natural occurrence of D 2 O and differences in chemical structure and physical properties compared to H 2 O, researchers have used D 2 O to study the effects of water on biomolecules and cells. Studies include effects of D 2 O on tobacco seed growth (Lewis, 1934), IgE-Mediated histamine release from human leukocytes (Gillespie and Lichtenstein, 1972), actin filament velocities (Chaen et al, 2001), protein flexibility (Cioni and Strambini, 2002), human pancreatic tumor cells (Hartmann et al, 2005), phospholipid membranes (Beranova et al, 2012), kinesin-1 gliding assay (Maloney et al, 2014), and stabilization of tubulin as observed previously in microtubule gliding assays (Panda et al, 2000) and in biochemical experiments on isolated tubulin proteins from beef brain (Houston et al, 1974) and goat brain (Das et al, 2008). Microtubules are polarized polymers of α/β tubulin heterodimers and undergo alternating phases of growth and shrinkage with sudden transitions between the two (Bartolini et al, 2005 In this paper we use the RBL-2H3 cell line, a typical mast cell model system (Thomas et al, 1992;Posner et al, 1995;Carroll-Portillo et al, 2010;Spendier et al, 2010), to start investigating this question.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the natural occurrence of D 2 O and differences in chemical structure and physical properties compared to H 2 O, researchers have used D 2 O to study the effects of water on biomolecules and cells. Studies include effects of D 2 O on tobacco seed growth (Lewis, 1934), IgE-Mediated histamine release from human leukocytes (Gillespie and Lichtenstein, 1972), actin filament velocities (Chaen et al, 2001), protein flexibility (Cioni and Strambini, 2002), human pancreatic tumor cells (Hartmann et al, 2005), phospholipid membranes (Beranova et al, 2012), kinesin-1 gliding assay (Maloney et al, 2014), and stabilization of tubulin as observed previously in microtubule gliding assays (Panda et al, 2000) and in biochemical experiments on isolated tubulin proteins from beef brain (Houston et al, 1974) and goat brain (Das et al, 2008). Microtubules are polarized polymers of α/β tubulin heterodimers and undergo alternating phases of growth and shrinkage with sudden transitions between the two (Bartolini et al, 2005).…”
Section: Introductionmentioning
confidence: 99%